Characterization of Ti6Al4V powders produced by different methods for selective electron beam melting - Liu Z.; Huang C.; Gao C.; Liu R.; Chen J.; Xiao Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Three different types of Ti6Al4V powders produced by electrode induction melting gas atomization (EIGA), plasma rotating electrode process (PREP), and plasma atomization (PA) were compared from these aspects: particle size distribution, particle shape, and microstructure. Theywere characterized by particle size and shape analyzer, scanning electron microscope, and X-ray diffraction. The results show some benefits of using PA Ti6Al4V powder in selective electron beam melting. The particle size distribution of these Ti6Al4V powders were bimodal, and the PA Ti6Al4V powder had the narrowest particle size span. The roundness and elongation, the bluntness index of the most analyzed Ti6Al4V powders were greater than 80%. There were 52%, 81%, and 93% Ti6Al4V powders without satellite, respectively. These particle shape results indicate that EIGA, PRER, and PA Ti6Al4V powders have good sphericity and low content of satellites. The flowability of PA (20.55 s/50 g) is better than that of EIGA (24.80 s/50 g) and PREP (25.76 s/50 g). The microstructure of Ti6Al4V powders was composed of martensite α′.